Salvage Laryngectomy, Decision Making to Optimize the Result: Neck Dissection? Salivary Bypass? Flap‐Assisted Closure?. (2nd September 2014) - Chepeha, Douglas B.; Gilbert, Ralph W.; Patel, Urjeet
Abstract : Program Description: How does a surgeon decide to optimize the outcome after performing a salvage laryngectomy? The goal of this miniseminar is to help the surgeon understand the decision‐making process for the reconstruction of the hypopharynx after salvage laryngectomy using evidence from 2 large national retrospective reviews. In addition, the role of withholding neck dissection to reduce morbidity will be discussed. Substantial time will be left at the end of the presentation to discuss specific case examples and have the faculty discuss perioperative and postoperative management. Educational Objectives: (1) Cite the current evidence for flap‐assisted closure for patients undergoing salvage laryngectomy. (2) Evaluate the risks and benefits of performing neck dissection for salvage patients. (3) Use case examples to demonstrate management relating to choice for neck dissection, use of the salivary bypass tube, and choice of flap‐assisted reconstruction.